2019
DOI: 10.1002/jcb.28975
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR‐224‐3p alleviates apoptosis from cerebral ischemia reperfusion injury by targeting FIP200

Abstract: Aims In previous studies, numerous differential microRNAs (miRNAs) in cerebral ischemic/reperfusion (I/R) injury were identified using the miRNA microarray analysis. However, the relationship between miRNA and cerebral I/R injury remains largely unknown. In this study, we investigated the function and explored the possible mechanism of miR‐224‐3p in cerebral I/R injury. Methods Oxygen glucose deprivation model in N2a cells were used to perform the cerebral I/R injury in vitro. Trypan blue staining, reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 20 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Overexpression of miR-424 could reduce ischemic brain injury through suppressing microglia activation [43]. Increasing miR-224-3p expression could attenuate cerebral ischemia/reperfusion injury by decreasing the expression of FAK family-interacting protein (FIP200) [44]. Our previous study demonstrated that upregulation of miR-145 could reduce astrocyte injury by decreasing the expression of AQP4 [23].…”
Section: Discussionmentioning
confidence: 98%
“…Overexpression of miR-424 could reduce ischemic brain injury through suppressing microglia activation [43]. Increasing miR-224-3p expression could attenuate cerebral ischemia/reperfusion injury by decreasing the expression of FAK family-interacting protein (FIP200) [44]. Our previous study demonstrated that upregulation of miR-145 could reduce astrocyte injury by decreasing the expression of AQP4 [23].…”
Section: Discussionmentioning
confidence: 98%
“…For example, overexpression of miR-224-3p alleviates apoptosis and then protects against cerebral ischemia reperfusion injury. 31 MiR-1247-3p protects brain stroke through inhibiting apoptosis. 32 MiR-25 negatively regulates cerebral ischemia/reperfusion injury-induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive production of ROS is shown to be closely related to the injury induced by cerebral ischemia-reperfusion, 20 22 which may contribute to brain damage. Moreover, oxidative stress-induced damage is the main cause of myocardial ischemia-reperfusion injury, and ROS levels are promoted in cardiac muscle tissue following ischemia reperfusion.…”
Section: Discussionmentioning
confidence: 99%